Children in the Practice of the International Criminal Court - Kovács, Péter (International Children's Rights, 2024)
The International Criminal Court (ICC) is paying enhanced attention to children by all its important institutions. The article would like to give an overview on the children related activity of (1) the Office of the Prosecutor, (2) the judiciary and (3) the Trust Fund for Victims. Children are victims of several crimes, inter alia child-soldiering, attacks against civilian population and different sexual and gender-based crimes. Special care is required when the ICC experts are collecting the children’s testimonies about crimes committed against them. The article gives an introduction into the children-related practice of the ICC and its considerations are based on quotations from the most important judicial decisions and the Policy Papers of the Prosecutor.Keywords: International Criminal Court, Rome Statute, OTP Policy Papers, crime of child-soldiering,‘ting-ting’, SGB crimes, ‘Do no harm’ principle, danger of retraumatization, Trust Fund for Victims, assistance mandate, reparation mandate, transgenerational harm